P122: The use of decision support tools in the implementation of the Prehospital Canadian Triage Acuity Score (Pre-CTAS). (2nd June 2016) - Smith, K.E.; Lobay, K.; Bullard, M.
Abstract : Introduction: The Prehospital Canadian Triage and Acuity Scale (Pre-CTAS) is based upon, and is consistent with, the CTAS (Canadian Triage and Acuity Scale). Paramedic-assigned Pre-CTAS scores using memory compared to Triage Nurse CTAS scores have previously demonstrated moderate inter-rater reliability. This is the first study to measure the effect of two different point-of-care decision support tools on the inter-rater reliability of paramedic assigned Pre-CTAS and Triage nurse CTAS scores.Methods: Paramedics were randomized to Pre-CTAS booklet or CTAS smartphone app during the one-year study period. Pre-CTAS scores assigned on arrival at hospital (AH) were compared with Triage Nurse CTAS scores and analyzed using Cohen's Kappa. Paramedics were then surveyed to assess the perceived utility and satisfaction with the decision support tools.Results: For 1663 patient transports, the weighted kappa score for Paramedic AH vs. Triage Nurse CTAS was fair at 0.38 (95% CI 0.35-0.41). For patients whose initial on-scene and AH Pre-CTAS scores did not change (n= 1405, 85%), Paramedic-Triage Nurse agreement was moderate at 0.43 (95% CI 0.39-0.46). The survey revealed that tools, when employed, helped assign scores; however accessing the additional resource was cumbersome or time consuming, and scores were occasionally assigned post clinical encounter.Conclusion: Point-of-care external decision support tools did not affect Pre-CTAS and ED CTAS agreement. These tools may add complexity or be perceived to add time to documentation within the delivery of clinical care if not implemented with adequate support. Future research needs to evaluate the impact of clinical decision support embedded within an electronic patient care record consistent with many ED information systems.